Detection of hypermethylation at H19DMR at amniocentesis in a fetus with overgrowth, distended abdomen and Beckwith-Wiedemann syndrome - Chih-Ping Chen; Schu-Rern Chern; Chien-Hsing Lin; Chin-Yuan Hsu; Hsiang-Yu Lin; Fang-Tzu Wu; Shin-Wen Chen; Wayseen Wang (Elsevier, 2021)
Objective: We present detection of hypermethylation at H19 differentially methylated region (DMR) at amniocentesis in a fetus with overgrowth, distended abdomen and Beckwith-Wiedemann syndrome (BWS). Case report: A 31-year-old, gravida 2, para 1, woman was referred for genetic counseling at 22 weeks of gestation because of fetal overgrowth with fetal biometry equivalent to 24 weeks of gestation and a distended abdomen with an abdominal circumference equivalent to 26 weeks of gestation. She did not undergo any assisted reproductive technology during this pregnancy. Amniocentesis was performed at 23 weeks of gestation. Conventional cytogenetic analysis revealed a karyotype of 46,XX. Array comparative genomic hybridization analysis on the DNA extracted from uncultured amniocytes revealed no genomic imbalance. Methylation analysis on the DNA extracted from amniocytes revealed hypermethylation at H19DMR [imprinting center 1 (IC1)] and normal methylation at KvDMR1 (IC2). The methylation test confirmed the diagnosis of BWS in the fetus. The parents decided to continue the pregnancy. At 36 weeks of gestation, a 4000-g female baby was delivered with macroglossia, ear tags and creases, and an enlarged liver, consistent with the phenotype of BWS. Conclusion: Prenatal diagnosis of fetal overgrowth should include a differential diagnosis of BWS, and methylation analysis of H19DMR (IC1) and KvDMR1 (IC2) is useful under such a circumstance.